Acid-alkali-resistant high-weather-resistant insulating powder coating, preparation method thereof and application of acid-alkali-resistant high-weather-resistant insulating powder coating to sound screens of high-speed guardrails
Corrosion resistant agents and weather resistant agents prepared through fluorocarbon resin and specific chemical reactions enhance the coating's weather resistance and acid and alkali corrosion resistance, solving the performance deficiencies of traditional coatings on highway guardrail sound barriers and achieving long-life protection.
Patent Information
- Application Number
- CN202511329900.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional coatings are insufficient in terms of weather resistance and acid and alkali corrosion resistance for highway guardrail sound barriers, making it difficult to meet the requirements for long-term protection.
Powder coatings composed of fluorocarbon resin, polyester resin, corrosion resistant agents, and weather resistant agents are prepared through specific chemical reactions to enhance the coating's resistance to acid and alkali corrosion and its weather resistance.
The prepared powder coating has excellent resistance to heat aging, light aging and acid and alkali corrosion, and is suitable for use in the field of high-speed guardrail sound barriers.
Smart Images

Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluorocarbon resin powder coating technology, specifically to an acid and alkali resistant, highly weather-resistant, insulating powder coating and its preparation method, as well as its application in high-speed guardrail sound barriers. Background Technology
[0002] Highway noise barriers are critical infrastructure for controlling traffic noise pollution. They are primarily composed of a metal substrate (such as galvanized steel or aluminum alloy) and a protective coating. These barriers are exposed to complex outdoor environments for extended periods, facing multiple performance challenges including extreme weather and chemical corrosion, as well as insulation and safety requirements. The metal structure of the noise barrier needs to be insulated from the guardrail (to prevent stray current corrosion). However, traditional coatings have insufficient insulation properties and are prone to peeling due to electrochemical corrosion. Furthermore, traditional powder coatings (such as pure epoxy and polyester) have poor weather resistance and insufficient resistance to acid and alkali corrosion, making it difficult to meet the long-life protection requirements of highway noise barriers in extreme environments.
[0003] Chinese invention patent CN110698950A discloses an insulating powder coating, which comprises the following raw material components in parts by weight: 60-80 parts epoxy resin, 20-30 parts silica powder, 5-10 parts calcium silicate, 3-5 parts ammonium polyphosphate, 1-3 parts benzoin, 20-40 parts curing agent, 1-5 parts accelerator, and 1-5 parts leveling agent. The insulating powder coating prepared by this invention has excellent insulation properties, but its resistance to acid and alkali corrosion and weather resistance are still insufficient. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the purpose of this invention is to provide an acid and alkali resistant, highly weather-resistant insulating powder coating, its preparation method, and its application in high-speed guardrail sound barriers.
[0005] To achieve the above objectives, the present invention provides the following technical solution: An acid and alkali resistant, highly weather-resistant insulating powder coating comprises the following raw materials in parts by weight: Fluorocarbon resin 15-25 parts, polyester resin 40-50 parts, curing agent 5-12 parts, accelerator 0.5-2 parts, corrosion resistant agent 3-8 parts, weather resistant agent 2-5 parts, leveling agent 1-2 parts, benzoin 0.3-1 parts, inorganic nanofiller 10-15 parts.
[0006] The corrosion resistant agent is prepared by the following method: S1: 4-Trifluoromethylphenol reacts with 6-bromo-1-hexene to form intermediate 1; the reaction equation is shown below: .
[0007] S2: Intermediate 1 reacts with m-chloroperoxybenzoic acid to form intermediate 2; the reaction equation is shown below. .
[0008] S3: Intermediate 2 reacts with the amino-terminated polyether to generate a corrosion-resistant agent; the reaction equation is shown below. .
[0009] In step S1, the molar ratio of 4-trifluoromethylphenol to 6-bromo-1-hexene is 1:(1.1-1.3); in step S2, the molar ratio of intermediate 1 to m-chloroperoxybenzoic acid is 1:(1.8-2.2); in step S3, the mass ratio of intermediate 2 to amino-terminated polyether is (1.8-1.95):1.
[0010] The weather-resistant agent is prepared by the following method: N1: The reaction of 1,5-dihydroxynaphthalene with epichlorohydrin yields intermediate A; the reaction equation is shown below: .
[0011] N2: Intermediate A reacts with 4-aminobutyltriethoxysilane to give intermediate B; the reaction equation is shown below. .
[0012] N3: Intermediate B reacts with benzothiazole-1-acetic acid to yield a weather-resistant agent; the reaction equation is shown below. .
[0013] In step N1, the molar ratio of 1,5-dihydroxynaphthalene to epichlorohydrin is 1:(2.1-2.3); in step N2, the molar ratio of intermediate A to 4-aminobutyltriethoxysilane is 1:(2.05-2.2); in step N3, the molar ratio of intermediate B to benzothiazol-1-acetic acid is 1:(2.1-2.2).
[0014] The curing agent is β-hydroxyalkylamide.
[0015] The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the leveling agent is BYK-333.
[0016] The inorganic nanofiller is silicon dioxide.
[0017] A method for preparing an acid and alkali resistant, highly weather-resistant insulating powder coating includes the following steps: (1) Weigh out the following by weight: 15-25 parts of fluorocarbon resin, 40-50 parts of polyester resin, 5-12 parts of curing agent, 0.5-2 parts of accelerator, 3-8 parts of corrosion resistant agent, 2-5 parts of weather resistant agent, 1-2 parts of leveling agent, 0.3-1 parts of benzoin, and 10-15 parts of inorganic nanofiller; (2) The inorganic nanofiller and KH-560 silane coupling agent are ultrasonically dispersed in anhydrous ethanol, filtered and dried to obtain the treated inorganic nanofiller; fluorocarbon resin, polyester resin, curing agent, accelerator, corrosion resistant agent, weather resistant agent, leveling agent, benzoin and the treated inorganic nanofiller are added to a high-speed mixer, mixed and then added to a twin-screw extruder to melt and extrude the material. The material is then pressed into tablets using a tablet press with a tap water cooling system, crushed in a high-speed pulverizer, and sieved to obtain an acid and alkali resistant, high weather resistant and insulating powder coating.
[0018] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: The powder coating prepared by this invention exhibits excellent resistance to heat aging, light aging, and acid and alkali corrosion. Specifically, the added corrosion resistant agent grafts fluorocarbon side chains onto the terminal amino polyether segments. The ultra-high stability of the carbon-fluorine bonds, the low surface energy and hydrophobicity of the fluorinated side chains, and the flexibility of the polyether segments containing numerous ether bonds synergistically improve the acid and alkali corrosion resistance of the powder coating. The added weather resistant agent grafts siloxane segments and benzotriazole structures onto the naphthalene ring. The rigidity and chemical stability of the naphthalene ring, the hydrophobicity and thermal stability of the siloxane segments, and the light stability of the benzotriazole structure synergistically improve the heat aging and light aging resistance of the acid and alkali resistant, high-weather-resistant insulating powder coating. The powder coating prepared in this application is suitable for the field of high-speed guardrail sound barriers. Detailed Implementation
[0019] The following description, in conjunction with specific embodiments, provides further details, but the present invention is not limited to these embodiments.
[0020] Example 1: Preparation of corrosion resistance agent: S1: 0.1 mol 4-trifluoromethylphenol, 0.11 mol 6-bromo-1-hexene, 0.28 mol anhydrous potassium carbonate, and 0.0011 mol 1 wt% tetrabutylammonium bromide were sequentially added to 300 mL of DMF. The mixture was reacted at 25 °C for 14 h, filtered, and rotary evaporated at 75 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V The mixture was purified by a 5:1 ratio and rotary evaporated at 50°C for 2 hours to obtain intermediate 1; its 1H NMR data are as follows: 1 H NMR (500 MHz, DMSO- d6) δ 7.67-7.61 (m, 2H), 7.14-7.08 (m, 2H),5.68 (s, 1H), 5.13-4.87 (m, 2H), 4.00 (s, 2H), 2.04 (s, 2H), 1.80 (s, 2H),1.58 (s, 2H); S2: 0.1 mol of intermediate 1 was mixed with 300 ml of anhydrous dichloromethane. Under ice bath conditions, 0.18 mol of m-chloroperoxybenzoic acid was added, and the mixture was stirred for 30 min. The temperature was then raised to 25 °C and reacted for 4 h. The reaction solution was washed successively with 200 ml of saturated sodium sulfite solution and 300 ml of saturated sodium bicarbonate solution, dried over 30 g of anhydrous magnesium sulfate, and rotary evaporated at 35 °C for 1 h to obtain intermediate 2. Its 1H NMR data are as follows: 1 H NMR (500 MHz, DMSO- d 6) δ 7.67-7.61 (m, 2H), 7.14-7.08 (m, 2H), 3.98 (d,J = 1.4 Hz, 2H), 3.32 (s, 1H), 2.89 (dd, J = 57.4, 5.0 Hz, 2H), 1.77 (dd, J =12.4, 3.1 Hz, 2H), 1.73-1.63 (m, 2H), 1.41 (d, J = 0.7 Hz, 2H); S3: Under nitrogen protection, 10g of terminal amino polyether (model ZT-143, number average molecular weight 440) was added to 200ml of toluene and stirred until homogeneous. 18g of intermediate 2 was slowly added in 3 batches (20min interval between each batch). 7g of triethylamine was added, and the mixture was heated to 55℃ and reacted for 6h. After cooling to room temperature, the mixture was washed with saturated sodium chloride solution (3×100ml), dried with 20g of anhydrous sodium sulfate, filtered, rotary evaporated at 70℃ for 2h, and vacuum dried at 70℃ for 5h to obtain the corrosion resistant agent.
[0021] Example 2: Preparation of corrosion resistance agent: S1: 0.1 mol 4-trifluoromethylphenol, 0.12 mol 6-bromo-1-hexene, 0.28 mol anhydrous potassium carbonate, and 0.4 g tetrabutylammonium bromide were added sequentially to 300 mL of DMF. The mixture was reacted at 25 °C for 13 h, filtered, and rotary evaporated at 75 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V Purify the mixture (5:1 ratio) and rotary evaporate at 50°C for 2 hours to obtain intermediate 1; S2: Mix 0.1 mol of intermediate 1 with 300 ml of anhydrous dichloromethane. Under ice bath conditions, add 0.2 mol of m-chloroperoxybenzoic acid. Stir for 30 min and then heat to 30 °C for 3 h. Wash the reaction solution successively with 200 ml of saturated sodium sulfite solution and 300 ml of saturated sodium bicarbonate solution. Dry with 30 g of anhydrous magnesium sulfate and rotary evaporate at 35 °C for 1 h to obtain intermediate 2. S3: Under nitrogen protection, 10g of terminal amino polyether (model ZT-143, number average molecular weight 440) was added to 200ml of toluene and stirred until homogeneous. 19g of intermediate 2 was slowly added in 3 batches (20min interval between each batch). 7g of triethylamine was added, and the mixture was heated to 60℃ and reacted for 5h. After cooling to room temperature, the mixture was washed with saturated sodium chloride solution (3×100ml), dried with 20g of anhydrous sodium sulfate, filtered, rotary evaporated at 70℃ for 2h, and vacuum dried at 70℃ for 5h to obtain the corrosion resistant agent.
[0022] Example 3: Preparation of corrosion resistance agent: S1: 0.1 mol 4-trifluoromethylphenol, 0.13 mol 6-bromo-1-hexene, 0.28 mol anhydrous potassium carbonate, and 0.0013 mol 1 wt% tetrabutylammonium bromide were sequentially added to 300 mL of DMF. The mixture was reacted at 30 °C for 12 h, filtered, and rotary evaporated at 75 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V Purify the mixture (5:1 ratio) and rotary evaporate at 50°C for 2 hours to obtain intermediate 1; S2: Mix 0.1 mol of intermediate 1 with 300 ml of anhydrous dichloromethane. Under ice bath conditions, add 0.22 mol of m-chloroperoxybenzoic acid. Stir for 30 min and then heat to 35 °C for 2 h. Wash the reaction solution successively with 200 ml of saturated sodium sulfite solution and 300 ml of saturated sodium bicarbonate solution. Dry with 30 g of anhydrous magnesium sulfate and rotary evaporate at 35 °C for 1 h to obtain intermediate 2. S3: Under nitrogen protection, 10g of terminal amino polyether (model ZT-143, number average molecular weight 440) was added to 200ml of toluene and stirred until homogeneous. 19.5g of intermediate 2 was slowly added in 3 batches (20min interval between each batch). 7g of triethylamine was added, and the mixture was heated to 65℃ and reacted for 4h. After cooling to room temperature, the mixture was washed with saturated sodium chloride solution (3×100ml), dried with 20g of anhydrous sodium sulfate, filtered, rotary evaporated at 70℃ for 2h, and vacuum dried at 70℃ for 5h to obtain the corrosion resistant agent.
[0023] Example 4: Preparation of weather-resistant agent: N1: Under nitrogen protection, 0.1 mol of 1,5-dihydroxynaphthalene, 0.21 mol of epichlorohydrin, and 6 mmol of tetrabutylammonium bromide were added to 200 mL of DMF, stirred until homogeneous, and reacted at 80 °C for 5 h. The temperature was then lowered to 65 °C, and 8 g of 20 wt% sodium hydroxide solution was slowly added dropwise over 30 min. The mixture was then cooled to room temperature and reacted for another 12 h. The mixture was then distilled under reduced pressure at 80 °C for 2 h, washed with deionized water (3 × 100 mL), and dried under vacuum at 70 °C for 10 h to obtain intermediate A. Its 1H NMR data are as follows: 1 H NMR (500 MHz, DMSO- d 6) δ7.98 (s, 2H), 7.22 (s, 2H), 7.02 (s, 2H), 4.29-4.18 (m, 4H), 3.87 (s, 2H), 2.97-2.77 (m, 4H); Under nitrogen protection, 0.205 mol of 4-aminobutyltriethoxysilane was added to 200 mL of anhydrous toluene. The mixture was stirred and mixed in an ice bath. 200 mL of anhydrous toluene solution containing 0.1 mol of intermediate A was slowly added dropwise over 30 min. Then, 0.2 mol of triethylamine was added, and the mixture was heated to 55 °C and reacted for 6 h. After cooling to room temperature, the mixture was dried over 20 g of anhydrous sodium sulfate, filtered, and distilled under reduced pressure at 70 °C for 2 h. 300 mL of anhydrous n-hexane was added, and the mixture was allowed to stand for 2 h to precipitate a solid. The solid was filtered, and the filter cake was washed with cold anhydrous n-hexane (3 × 100 mL). The solid was then dried under vacuum at 60 °C for 8 h to obtain intermediate B. Its 1H NMR data are as follows: 1 H NMR (500 MHz, DMSO- d 6)δ 7.98 (s, 2H), 7.22 (s, 2H), 7.03 (s, 2H), 4.65 (d, J = 5.0 Hz, 2H), 4.05-3.99 (m, 2H), 3.98 (d, J = 12.3 Hz, 4H), 3.81 (s, 2H), 3.64-3.54 (m, 12H), 2.81-2.71 (m, 4H), 2.70-2.62 (m, 4H), 1.79-1.66 (m, 4H), 1.57-1.44 (m, 4H), 1.28 (s, 4H), 1.20 (s, 18H); N3: Under nitrogen protection, 600 ml of anhydrous DMF and 0.21 mol of benzothiazole-1-acetic acid were stirred and mixed thoroughly. 48 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 29 g of N-hydroxysuccinimide were weighed and mixed, then added in 5 equal batches (5 min apart) to the DMF solution of benzothiazole-1-acetic acid. The mixture was stirred and activated in an ice bath for 45 min. 0.1 mol of intermediate B was added to 400 ml of anhydrous DMF and stirred thoroughly. The activated benzothiazole-1-acetic acid DMF solution was slowly added dropwise over 1 h. The reaction was carried out at 25 °C for 8 h (using 0.1 M...) during the reaction. The pH of the solution was maintained between 7.2 and 7.6 using an HCl / NaOH solution. 500 ml of ice water was added, and the mixture was stirred until homogeneous. Then, 2000 ml of ethyl acetate was added. The mixture was separated, and the organic phase was washed successively with deionized water (3 × 250 ml) and saturated saline (1 × 250 ml). 80 g of anhydrous magnesium sulfate was added to the organic phase for drying. The mixture was filtered, distilled under reduced pressure at 60 °C for 1.5 h, and then dried under vacuum at 60 °C for 12 h to obtain the weathering agent. Its 1H NMR data are as follows: 1 H NMR (500 MHz, DMSO- d 6) δ 7.98 (s,2H), 7.94 (d, J = 0.6 Hz, 2H), 7.62 (d, J = 0.5 Hz, 2H), 7.49 (s, 2H), 7.46(s, 2H), 7.22 (s, 2H), 7.01 (s, 2H), 5.26-5.16 (m, 4H), 4.72 (s, 2H), 4.25-4.10 (m, 4H), 3.64-3.61 (m, 2H), 3.57 (d, J = 12.4 Hz, 12H), 2.86 (qd, J =12.4, 0.5 Hz, 4H), 2.72-2.60 (m, 4H), 1.79-1.65 (m, 4H), 1.58-1.44 (m, 4H), 1.28 (s, 4H), 1.20 (s, 18H).
[0024] Example 5 Preparation of weather-resistant agent: N1: Under nitrogen protection, 0.1 mol of 1,5-dihydroxynaphthalene, 0.22 mol of epichlorohydrin and 6 mmol of tetrabutylammonium bromide were added to 200 ml of DMF, stirred and mixed, and reacted at 85 °C for 4 h. The temperature was then lowered to 65 °C, and 8 g of 20 wt% sodium hydroxide solution was slowly added dropwise over 30 min. The mixture was then cooled to room temperature and reacted for another 12 h. The mixture was then distilled under reduced pressure at 80 °C for 2 h, washed with deionized water (3 × 100 ml), and dried under vacuum at 70 °C for 10 h to obtain intermediate A. Under nitrogen protection, 0.21 mol of 4-aminobutyltriethoxysilane was added to 200 ml of anhydrous toluene and stirred until homogeneous in an ice bath. 200 ml of anhydrous toluene solution containing 0.1 mol of intermediate A was slowly added dropwise over 30 min. Then, 0.2 mol of triethylamine was added, and the mixture was heated to 60 °C and reacted for 5 h. After cooling to room temperature, the mixture was dried over 20 g of anhydrous sodium sulfate, filtered, and distilled under reduced pressure at 70 °C for 2 h. 300 ml of anhydrous n-hexane was added, and the mixture was allowed to stand for 2 h to precipitate a solid. The solid was filtered, and the filter cake was washed with cold anhydrous n-hexane (3 × 100 ml) and dried under vacuum at 60 °C for 8 h to obtain intermediate B. N3: Under nitrogen protection, 600 ml of anhydrous DMF and 0.215 mol of benzothiazole-1-acetic acid were stirred and mixed thoroughly. 49 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 29.7 g of N-hydroxysuccinimide were weighed, mixed, and then added in 5 equal batches (5 min apart) to the DMF solution of benzothiazole-1-acetic acid. The mixture was stirred and activated in an ice bath for 45 min. 0.1 mol of intermediate B was added to 400 ml of anhydrous DMF and stirred thoroughly. The activated benzothiazole-1-acetic acid DMF solution was slowly added dropwise over 1 h. The reaction was carried out at 25 °C for 8 h (using 0.1 M...) during the reaction. (Maintain the pH of the solution with HCl / NaOH solution between 7.2 and 7.6), add 500 ml of ice water, stir to mix well, then add 2000 ml of ethyl acetate, separate the liquid and organic phase, wash the organic phase successively with deionized water (3 × 250 ml) and saturated brine (1 × 250 ml), add 80 g of anhydrous magnesium sulfate to the organic phase to dry, filter, distill under reduced pressure at 60 °C for 1.5 h, and dry under vacuum at 60 °C for 12 h to obtain the weathering agent.
[0025] Example 6 Preparation of weather-resistant agent: N1: Under nitrogen protection, 0.1 mol of 1,5-dihydroxynaphthalene, 0.23 mol of epichlorohydrin and 6 mmol of tetrabutylammonium bromide were added to 200 ml of DMF, stirred and mixed, and reacted at 90 °C for 3 h. The temperature was then lowered to 65 °C, and 8 g of 20 wt% sodium hydroxide solution was slowly added dropwise over 30 min. The mixture was then cooled to room temperature and reacted for another 12 h. The mixture was then distilled under reduced pressure at 80 °C for 2 h, washed with deionized water (3 × 100 ml), and dried under vacuum at 70 °C for 10 h to obtain intermediate A. Under nitrogen protection, 0.22 mol of 4-aminobutyltriethoxysilane was added to 200 ml of anhydrous toluene and stirred until homogeneous in an ice bath. 200 ml of anhydrous toluene solution containing 0.1 mol of intermediate A was slowly added dropwise over 30 min. Then, 0.2 mol of triethylamine was added, and the mixture was heated to 65 °C and reacted for 4 h. After cooling to room temperature, the mixture was dried over 20 g of anhydrous sodium sulfate, filtered, and distilled under reduced pressure at 70 °C for 2 h. 300 ml of anhydrous n-hexane was added, and the mixture was allowed to stand for 2 h to precipitate a solid. The solid was filtered, and the filter cake was washed with cold anhydrous n-hexane (3 × 100 ml) and dried under vacuum at 60 °C for 8 h to obtain intermediate B. N3: Under nitrogen protection, 600 ml of anhydrous DMF and 0.22 mol of benzothiazole-1-acetic acid were stirred and mixed thoroughly. 50 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 30 g of N-hydroxysuccinimide were weighed, mixed, and then added in 5 equal batches (5 min apart) to the DMF solution of benzothiazole-1-acetic acid. The mixture was stirred and activated in an ice bath for 45 min. 0.1 mol of intermediate B was added to 400 ml of anhydrous DMF and stirred thoroughly. The activated benzothiazole-1-acetic acid DMF solution was slowly added dropwise over 1 h. The reaction was carried out at 30 °C for 7 h (using 0.1 M N2 solution during the reaction). (Maintain the pH of the solution with HCl / NaOH solution between 7.2 and 7.6), add 500 ml of ice water, stir to mix well, then add 2000 ml of ethyl acetate, separate the liquid and organic phase, wash the organic phase successively with deionized water (3 × 250 ml) and saturated brine (1 × 250 ml), add 80 g of anhydrous magnesium sulfate to the organic phase to dry, filter, distill under reduced pressure at 60 °C for 1.5 h, and dry under vacuum at 60 °C for 12 h to obtain the weathering agent.
[0026] Example 7: Preparation of acid and alkali resistant, highly weather-resistant insulating powder coating: (1) Weigh the following by weight: 150g fluorocarbon resin, 400g polyester resin, 50g curing agent (β-hydroxyalkylamide), 5g accelerator (2,4,6-tris(dimethylaminomethyl)phenol), 30g corrosion resistant agent (prepared in Example 1), 20g weather resistant agent (prepared in Example 4), 10g leveling agent (BYK-333), 3g benzoin, and 100g inorganic nanofiller (silica); (2) The inorganic nanofiller and 1g KH-560 silane coupling agent were ultrasonically dispersed in 500ml anhydrous ethanol for 30min, filtered, and dried at 80℃ for 2h to obtain the treated inorganic nanofiller; fluorocarbon resin, polyester resin, curing agent, accelerator, corrosion resistant agent, weather resistant agent, leveling agent, benzoin and the treated inorganic nanofiller were added to a high-speed mixer and mixed at 800rpm for 30min. The mixture was then added to a twin-screw extruder to melt and extrude the material (extrusion section temperature 150℃, screw speed 400rpm). The material was then tableted using a tablet press with a tap water cooling system and placed in a high-speed pulverizer. The tablets were pulverized at 2000rpm for 20min and passed through an 180-mesh sieve to obtain an acid and alkali resistant, weather resistant and insulating powder coating.
[0027] Example 8: Preparation of acid and alkali resistant, highly weather-resistant insulating powder coating: (1) Weigh the following by weight: 200g fluorocarbon resin, 450g polyester resin, 90g curing agent (β-hydroxyalkylamide), 15g accelerator (2,4,6-tris(dimethylaminomethyl)phenol), 50g corrosion resistant agent (prepared in Example 2), 35g weather resistant agent (prepared in Example 5), 15g leveling agent (BYK-333), 7g benzoin, and 130g inorganic nanofiller (silica); (2) The inorganic nanofiller and 1.5g KH-560 silane coupling agent were ultrasonically dispersed in 500ml anhydrous ethanol for 30min, filtered, and dried at 80℃ for 2h to obtain the treated inorganic nanofiller; fluorocarbon resin, polyester resin, curing agent, accelerator, corrosion resistant agent, weather resistant agent, leveling agent, benzoin and the treated inorganic nanofiller were added to a high-speed mixer and mixed at 800rpm for 30min. The mixture was then added to a twin-screw extruder to melt and extrude the material (extrusion section temperature 155℃, screw speed 350rpm). The material was tableted using a tablet press with a tap water cooling system and then placed in a high-speed pulverizer and pulverized at 2000rpm for 20min. The mixture was then passed through a 190-mesh sieve to obtain an acid and alkali resistant, weather resistant and insulating powder coating.
[0028] Example 9: Preparation of acid and alkali resistant, highly weather-resistant insulating powder coating: (1) Weigh the following by weight: 250g fluorocarbon resin, 500g polyester resin, 120g curing agent (β-hydroxyalkylamide), 20g accelerator (2,4,6-tris(dimethylaminomethyl)phenol), 80g corrosion resistant agent (prepared in Example 3), 50g weather resistant agent (prepared in Example 6), 20g leveling agent (BYK-333), 10g benzoin, and 150g inorganic nanofiller (silica); (2) The inorganic nanofiller and 2g KH-560 silane coupling agent were ultrasonically dispersed in 500ml anhydrous ethanol for 30min, filtered, and dried at 80℃ for 2h to obtain the treated inorganic nanofiller; fluorocarbon resin, polyester resin, curing agent, accelerator, corrosion resistant agent, weather resistant agent, leveling agent, benzoin and the treated inorganic nanofiller were added to a high-speed mixer and mixed at 800rpm for 30min. The mixture was then added to a twin-screw extruder to melt and extrude the material (extrusion section temperature 160℃, screw speed 300rpm). The material was then tableted using a tablet press with a tap water cooling system and placed in a high-speed pulverizer. The tablets were pulverized at 2000rpm for 20min and passed through a 200-mesh sieve to obtain an acid and alkali resistant, weather resistant and insulating powder coating.
[0029] Comparative Example 1 The raw material composition and preparation method of the acid and alkali resistant and weather resistant insulating powder coating are basically the same as those in Example 8. The difference is that no corrosion resistant agent is added to the components.
[0030] Comparative Example 2 The raw material composition and preparation method of the acid and alkali resistant and weather-resistant insulating powder coating are basically the same as those in Example 8. The difference is that no weather-resistant agent is added to the components.
[0031] Comparative Example 3 The raw material composition and preparation method of the acid and alkali resistant, high weather resistant insulating powder coating are basically the same as those in Example 8, except that the corrosion resistant agent is replaced with an equal weight of corrosion resistant agent prepared by the following method: The preparation method of the corrosion resistant agent is basically the same as that in Example 2, except that 4-trifluoromethylphenol in step S1 is replaced with an equimolar amount of 4-fluorophenol.
[0032] Comparative Example 4 The raw material composition and preparation method of the acid and alkali resistant, high weather resistant insulating powder coating are basically the same as those in Example 8, except that the corrosion resistant agent is replaced with an equal weight of corrosion resistant agent prepared by the following method: The preparation method of the corrosion resistant agent is basically the same as that in Example 2, except that the preparation steps in step S3 are as follows: Under nitrogen protection, 9.8 g of ZD-140 amino-terminated polyether (functionality 2, number average molecular weight 430, purchased from Zibo Zhengda Polyurethane Co., Ltd.) was added to 200 ml of toluene and stirred until homogeneous. 13 g of intermediate 2 was slowly added in three batches (20 min apart). 7 g of triethylamine was added, and the mixture was heated to 60 °C and reacted for 5 h. After cooling to room temperature, the mixture was washed with saturated sodium chloride solution (3 × 100 ml), dried with 10 g of anhydrous sodium sulfate for 2 h, filtered, rotary evaporated at 70 °C for 2 h, and vacuum dried at 70 °C for 5 h to obtain the corrosion resistant agent.
[0033] Comparative Example 5 The raw material composition and preparation method of the acid and alkali resistant, high weather-resistant insulating powder coating are basically the same as those in Example 8, except that the weather-resistant agent is replaced with an equal weight of weather-resistant agent prepared by the following method: The preparation method of the weathering agent is basically the same as that in Example 5, except that 1,5-dihydroxynaphthalene in step N1 is replaced with an equimolar amount of hydroquinone.
[0034] Comparative Example 6 The raw material composition and preparation method of the acid and alkali resistant, high weather-resistant insulating powder coating are basically the same as those in Example 8, except that the weather-resistant agent is replaced with an equal weight of weather-resistant agent prepared by the following method: The preparation method of the weathering agent is basically the same as that in Example 5, except that 4-aminobutyltriethoxysilane in step N2 is replaced with an equimolar amount of 4-aminobutyltrimethoxysilane (CAS No.: 15005-59-1).
[0035] Comparative Example 7 The raw material composition and preparation method of the acid and alkali resistant, high weather-resistant insulating powder coating are basically the same as those in Example 8, except that the weather-resistant agent is replaced with an equal weight of weather-resistant agent prepared by the following method: The preparation method of the weathering agent is basically the same as that in Example 5, except that benzothiazole-1-acetic acid in step N3 is replaced with an equimolar amount of indole-1-acetic acid.
[0036] The polyester resin used in the embodiments and comparative examples of this application is model YC8588, produced by Anhui Yongchang New Material Technology Co., Ltd.; the fluorocarbon resin is model JF-2X; the amino-terminated polyether is model ZT-143 amino-terminated polyether, purchased from Zibo Zhengda Polyurethane Co., Ltd.; and the silica is model HB-132, produced by Hubei Huifu Nanomaterials Co., Ltd.
[0037] The acid and alkali resistant and weather-resistant insulating powder coatings prepared in Examples 7-9 and Comparative Examples 1-7 were tested for acid and alkali resistance, heat aging resistance, and light aging resistance. The test results are shown in Table 1.
[0038] Sample preparation: Samples were prepared in accordance with the HG / T 2006-2006 standard. The substrate was carbon steel plate (1 mm thick, 150 mm × 100 mm in size). The coating thickness was 0.06 mm. The prepared sample was placed in a forced-air drying oven and cured at 180°C for 15 min. Then, the temperature was lowered to 23°C and placed at 50% relative humidity for 24 h to obtain the sample.
[0039] Acid resistance (immersion time 240h) and alkali resistance (immersion time 500h) were tested according to HG / T 2006-2006 standard. Heat aging performance was tested: the samples were placed in an 80℃ forced-air drying oven for 500h for high-temperature heat aging. After the test, the samples were placed at room temperature for 1h to obtain the heat-aged samples. The adhesion grade of the samples before and after heat aging was tested according to HG / T 2006-2006 standard.
[0040] Light aging resistance test: The sample is placed in a QUV accelerated aging test chamber, with an irradiance (W / m²). 2 The gloss level ( / nm) was 0.76, the ultraviolet wavelength was 340nm, the temperature was 60℃, and the test time was 1200h. The resulting sample was photoaged. The gloss level of the sample before and after photoaging was tested using a YG60S60° gloss meter.
[0041]
[0042] As can be seen from Table 1, the acid and alkali resistant and weather-resistant insulating powder coatings prepared in Examples 7-9 of this application have excellent acid and alkali resistance, heat aging resistance and light aging resistance.
[0043] The powder coatings prepared in Examples 7-9 exhibit excellent acid and alkali resistance because the corrosion resistant agents prepared in these examples contain trifluoromethyl groups in their side chains, which can form a dense protective layer of fluorine atoms on the molecular surface, preventing H from entering the atmosphere. + (Acidic) and OH- - The fluorinated side chains exhibit low surface energy, making the coating surface hydrophobic and significantly reducing the wetting and penetration of acid and alkali solutions. Furthermore, the polyether segments contain numerous ether bonds with high rotational freedom, which can alleviate internal stress caused by coating curing or temperature changes, preventing the formation of corrosive media penetration channels due to cracking. In contrast, Comparative Example 1 did not add any corrosion inhibitor; the corrosion inhibitor prepared in Comparative Example 3 lacked trifluoromethyl side chains; and the corrosion inhibitor prepared in Comparative Example 4 using ZD-140 terminal amino polyether with a functionality of 2 had fewer polyether segments, resulting in poorer acid and alkali corrosion resistance of the powder coating.
[0044] The powder coatings prepared in Examples 7-9 exhibit excellent heat and light aging resistance, primarily due to the grafting of siloxane segments and benzotriazole structures onto the naphthalene ring in the weathering agents prepared in these examples. The rigidity and chemical stability of the naphthalene ring, the hydrophobicity and thermal stability of the siloxane segments, and the photostability of the benzotriazole structure synergistically enhance the heat and light aging resistance of the powder coatings. In contrast, Comparative Example 2, which did not contain a weathering agent, produced powder coatings with inferior heat and light aging resistance compared to the examples. Comparative Example 5 used a weathering agent prepared with hydroquinone, which reduced the rigid ring and weakened its rigidity and chemical stability. Comparative Example 6 used a weathering agent prepared with 4-aminobutyltrimethoxysilane, which shortened the siloxane segments, resulting in decreased thermal stability and consequently, reduced heat aging resistance of the powder coating. The weathering agent prepared in Comparative Example 7 lacked the benzotriazole structure, leading to decreased photostability and thus poorer photostability of the powder coating.
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. An acid and alkali resistant, highly weather-resistant insulating powder coating, characterized in that, The ingredients include the following parts by weight: Fluorocarbon resin 15-25 parts, polyester resin 40-50 parts, curing agent 5-12 parts, accelerator 0.5-2 parts, corrosion resistant agent 3-8 parts, weather resistant agent 2-5 parts, leveling agent 1-2 parts, benzoin 0.3-1 parts, inorganic nanofiller 10-15 parts; The corrosion resistant agent is prepared by the following method: S1: 4-Trifluoromethylphenol reacts with 6-bromo-1-hexene to form intermediate 1. S2: Intermediate 1 is converted into intermediate 2 under the action of m-chloroperoxybenzoic acid. S3: Intermediate 2 reacts with amino-terminated polyether to generate a corrosion resistant agent; The weather-resistant agent is prepared by the following method: N1: 1,5-Dihydroxynaphthalene reacts with epichlorohydrin to give intermediate A. N2: Intermediate A reacts with 4-aminobutyltriethoxysilane to give intermediate B. N3: Intermediate B reacts with benzothiazole-1-acetic acid to obtain a weathering agent.
2. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, In step S1, the molar ratio of 4-trifluoromethylphenol to 6-bromo-1-hexene is 1:(1.1-1.3).
3. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, In step S2, the molar ratio of intermediate 1 to m-chloroperoxybenzoic acid is 1:(1.8-2.2).
4. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, In step S3, the mass ratio of intermediate 2 to amino-terminated polyether is (1.8-1.95):
1.
5. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, In step N1, the molar ratio of 1,5-dihydroxynaphthalene to epichlorohydrin is 1:(2.1-2.3); in step N2, the molar ratio of intermediate A to 4-aminobutyltriethoxysilane is 1:(2.05-2.2); in step N3, the molar ratio of intermediate B to benzothiazol-1-acetic acid is 1:(2.1-2.2).
6. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, The curing agent is a β-hydroxyalkylamide.
7. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the leveling agent is BYK-333.
8. The acid and alkali resistant, highly weather-resistant insulating powder coating according to claim 1, characterized in that, The inorganic nanofiller is silicon dioxide.
9. A method for preparing an acid and alkali resistant, highly weather-resistant insulating powder coating according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Weigh out the following by weight: 15-25 parts of fluorocarbon resin, 40-50 parts of polyester resin, 5-12 parts of curing agent, 0.5-2 parts of accelerator, 3-8 parts of corrosion resistant agent, 2-5 parts of weather resistant agent, 1-2 parts of leveling agent, 0.3-1 parts of benzoin, and 10-15 parts of inorganic nanofiller; (2) The inorganic nanofiller and KH-560 silane coupling agent are ultrasonically dispersed in anhydrous ethanol, filtered and dried to obtain the treated inorganic nanofiller; fluorocarbon resin, polyester resin, curing agent, accelerator, corrosion resistant agent, weather resistant agent, leveling agent, benzoin and the treated inorganic nanofiller are added to a high-speed mixer, mixed and then added to a twin-screw extruder to melt and extrude the material. The material is then pressed into tablets using a tablet press with a tap water cooling system, crushed in a high-speed pulverizer, and sieved to obtain an acid and alkali resistant, high weather resistant and insulating powder coating.
10. The application of the acid and alkali resistant, high weather resistant insulating powder coating as described in claims 1-8 in the application of sound barriers for highway guardrails.
Citation Information
Patent Citations
Insulating powder coating
CN110698950A
Cited By
Flame-retardant corrosion-resistant coating and preparation method thereof
CN121450202A